P/F Ratio is a Better Predictor for Non-Invasive Ventilation Failure and Length of Stay in Patients with Community-Acquired Pneumonia - Hapsari, Brigitta Anindita Devi; Roxanne, Olivia Geraldine; Reviono, Reviono; Adhiputri, Artrien; Apriningsih, Hendrastutik; Rahayu, Nur Indah; Vagheggini, Guido (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: Community-acquired pneumonia (CAP) can deteriorate into respiratory failure requiring immediate ventilatory intervention. This study compared the performance of the PaO2/FiO2 (P/F) ratio, the ratio of oxygen saturation (ROX) index, and the heart rate, acidosis, consciousness, oxygenation, and respiratory rate (HACOR) score in predicting non-invasive ventilation (NIV) failure and length of hospital stay in patients diagnosed with CAP. Methods: This study was conducted at Universitas Sebelas Maret Hospital, Surakarta, from March to September 2023. All patients diagnosed with CAP who were eligible for NIV were recruited. Each patient's age, sex, comorbidities, vital signs, pneumonia severity index (PSI), blood urea, bilirubin, hematocrit, blood sodium, P/F ratio, ROX index, and HACOR score were measured within the first 24 hours of NIV. Subsequently, the correlations between these variables and NIV failure (intubation or mortality) and length of hospital stay were assessed. Results: The P/F ratio, ROX index, and HACOR score were not correlated with intubation or length of stay. The P/F ratio was correlated with mortality (p = 0.040), whereas the other scores were not. Higher body temperature was correlated with intubation (p = 0.032). PSI was correlated with both mortality (p = 0.033) and length of hospital stay (p = 0.009). Conclusion: The P/F ratio is superior to the ROX index and HACOR score in predicting mortality in patients with pneumonia-related respiratory failure treated with NIV. Since it is simple and accessible, measuring the P/F ratio within the first 24 hours of NIV is recommended to identify a patient's risk of NIV failure and apply appropriate monitoring.